La valorización de acciones en el ejercicio del derecho de separación de accionistas en una sociedad anónima - Ferrero Álvarez-Calderón, Guillermo (2020)
The valuation methodology of shares in the exerci-se of the right of separation of a shareholder from the company has generated debate and is treated differently in a number of legislations. In this article, the author analyzes the various methods for the valuation of shares and their treatment in di-fferent countries, making reference to relevant jurisprudence and legislation on the matter.In addition to that, the author enters to the world of corporate finance in order to perform an analysis of Cash Flow at Present Value and the use of that valuation method in new business fields such as technology.